HAMIL SEHAT DAN BUGAR DENGAN PRENATAL GENTLE YOGA KOMBINASI DENGAN METODE RELAKSASI HYPNOBIRTHING - Yusri Dwi Lestari (STIKES NGUDIA HUSADA MADURA, 2022)
Pregnancy is a physiological condition. During pregnancy there is discomfort which is a result of the physiological adaptation process of the mother's body system to her pregnancy. Discomfort that is still within normal limits can turn out to be abnormal due to the mother's unpreparedness for her pregnancy. Healthy pregnant women will have an impact on optimal fetal development. Labor preparation also starts from pregnancy. Prental yoga and relaxation is a promotive and preventive effort to improve the health of the mother so that she can adapt to physical and psychological changes during pregnancy and prepare for labor. This activity will be carried out in the Karanganyarpolindes area where pregnant women in the Karanganyarpolindes area have never been trained in prenatal yoga to overcome discomfort, what pregnant women do when experiencing discomfort during pregnancy is to come to the midwife or health center and get medicine.The services will be in the form of physical exercise and relaxation with prenatal gentle yoga combined with relaxation techniques from hypnobirthing which aims to reduce physical discomfort and reduce anxiety, especially during pregnancy and childbirth. Keywords: Yoga, relaxation, pregnancy